Acute Renal Failure as Part of Multi-Organ Failure: How Long We Should Wait before We Intervene? A Dissection of Studies (Journal of Enam Medical College, 2015)
Mortality rate in multisystem organ failure (MOF) is very high. Acute renal failure is an important part of MOF. In this special feature article I have aimed to streamline the achievements of different studies on continuous renal replacement therapy (CRRT) for a fruitful outcome. For this I have gone for retrospective evaluation of the studies reached through PubMed, internet alert system of different journals, proceedings of conferences on CRRT and personal communication with the experts in this field. I have evaluated the outcome of studies to explore the causes of failure to achieve a positive result and to identify the positive gains of studies. Finally, I have compiled the positive gains to outline a new strategy for future study and greater achievement. The findings of evaluation led to the conclusion that while planning for initiation of CRRT, multiple strategies should be targeted. The strategy should involve early initiation of CRRT guided by new markers of acute kidney injury (AKI), continuous venovenous hemofiltration (CVVH) modality, optimum intensity (intensity should be adequate enough to improve hemodynamics within a targeted period), selection of an effective filter membrane. Elderly patients should be studied in a different group. Cardiac patients with AKI should not be studied in the same group along with the patients with sepsis DOI: http://dx.doi.org/10.3329/jemc.v5i1.21496 J Enam Med Col 2015; 5(1): 39-43